Heterogeneity of management practices surrounding operable gallbladder cancer – results of the OMEGA-S international HPB surgical survey. Issue 11 (November 2022) - Balakrishnan, Anita; Jah, Asif; Lesurtel, Mickael; Andersson, Bodil; Gibbs, Paul; Harper, Simon J.F.; Huguet, Emmanuel L.; Kosmoliaptsis, Vasilis; Liau, Siong S.; Praseedom, Raaj K.; Ramia, Jose M.; Branes, Alejandro; et al.
Abstract: Background: Gallbladder cancer (GBC) is an aggressive, uncommon malignancy, with variation in operative approaches adopted across centres and few large-scale studies to guide practice. We aimed to identify the extent of heterogeneity in GBC internationally to better inform the need for future multicentre studies. Methods: A 34-question online survey was disseminated to members of the European-African Hepatopancreatobiliary Association (EAHPBA), American Hepatopancreatobiliary Association (AHPBA) and Asia–Pacific Hepatopancreatobiliary Association (A-PHPBA) regarding practices around diagnostic workup, operative approach, utilization of neoadjuvant and adjuvant therapies and surveillance strategies. Results: Two hundred and three surgeons responded from 51 countries. High liver resection volume units (>50 resections/year) organised HPB multidisciplinary team discussion of GBCs more commonly than those with low volumes (p < 0.0001). Management practices exhibited areas of heterogeneity, particularly around operative extent. Contrary to consensus guidelines, anatomical liver resections were favoured over non-anatomical resections for T3 tumours and above, lymphadenectomy extent was lower than recommended, and a minority of respondents still routinely excised the common bile duct or port sites. Conclusion: Our findings suggest some similarities in the management of GBC internationally, but also specific areas of practice which differed from published guidelines. Transcontinental collaborative studies on GBC are necessary to establish evidence-based practice to minimise variation and optimise outcomes.